Rhizoecus americanus (Hambleton) e Pseudaulacaspis cockerelli (Cooley) (Homoptera Coccoidea) dannosi alle piante ornamentali in Italia (Bollettino di zoologia agraria e bachicoltura, 2024)
Rhizoecus americanus (Hambleton) (Homoptera: Pseudococcidae), collected on Saintpaulia sp. and Pseudaulacaspis cockerelli (Cooley) (Homoptera: Diaspididae), collected on Phoenix roebelenii, are reported. For each species, not yet recorded for the Italian fauna, brief data on morphology, taxonomy, distribution and a key for their identification are also given.
Keywords: ornamental plants; scale insects; Italy